2013
DOI: 10.5846/stxb201207080956
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three forest restoration approaches on plant diversity in red soil region, southern China

Abstract: Plant diversity has important ecosystem function in forest ecosystem. Forest restoration approaches can impact plant diversity, especially the understory plant diversity. We studied the floristic characteristics, plant community structure and diversity of three forest restoration approaches in red soil region of southern China, which included introduced species slash pine (Pinus elliottii) plantations, native species Masson pine (Pinus massoniana) plantations and natural secondary forests. For each forest rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…and or is more artificial disturbed forest higher? (Mao & Zhu, 2006;Wang et al, 2013). These research results proved that the plant diversity of natural forest or long time natural restoration forest is obviously higher than artificial forest or more artificial disturbed forest (Huang et al, 2016a;Huang et al, 2016b;Liang et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…and or is more artificial disturbed forest higher? (Mao & Zhu, 2006;Wang et al, 2013). These research results proved that the plant diversity of natural forest or long time natural restoration forest is obviously higher than artificial forest or more artificial disturbed forest (Huang et al, 2016a;Huang et al, 2016b;Liang et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…The above research results are better evidences and references to the argument on whether natural forests and naturally restored forests, artificial forests, or more artificially disturbed forests had higher biodiversity [28] [29]. The research results showed that plant diversity of natural or long-term naturally restored forests was obviously higher than that of artificial forests or more artificially disturbed forest.…”
Section: Discussionmentioning
confidence: 92%